TUGAS BADAN PENGAWAS PEMILIHAN UMUM KOTA KUPANG DALAM PENGAWASAN DESAIN BALIHO CALON LEGISLATIF PADA PEMILU 2024-2029 - Imanuel V Listanto; Josef M Monteiro; Mario A Lawung (Petitum Law Journal, 2026)
This research explores the implementation of supervisory duties carried out by Bawaslu Kupang City in monitoring the design of campaign billboards used by legislative candidates during the 2024–2029 general election period. The study adopts an empirical legal approach with socio-legal and statutory methods, involving interviews and document analysis. The findings indicate that Bawaslu plays a crucial role in ensuring the design, placement, and content of billboards comply with electoral regulations. However, the supervision process faces challenges such as limited human resources and inadequate use of technology. In addition, violations often occur due to deliberate actions by candidates or teams, seeking political visibility. This study concludes that strengthening institutional capacity, public awareness, and stricter law enforcement are essential to improve the quality of democratic elections.